Early Detection Application for Assessing Pre-Eclampsia Risk in Expectant Mothers - Aprina, Aprina; Anita, Anita; Titi Astuti (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to evaluate the effectiveness of the early detection of pre-eclampsia in pregnant women. METHODOLOGY: This study focuses on pregnant women in Tanggamus Regency, Lampung, using early detection tools of pre-eclampsia and anthropometric examination. A total of 198 participants were enrolled in the 3rd to 4th trimester. Statistical analysis was used to develop an online model to estimate pre-eclampsia risk. The application uses the waterfall method, which involves requirements, design, implementation, verification, and maintenance. RESULTS: The findings from the data analysis conducted in accordance with ISO 25010 standards evaluated two specific dimensions: functional suitability and usability. It was determined that the Pre-eclampsia Early Detection application software achieved an overall score of 88%. Using this model, the risks that pregnant women and the interventions they will experience will be known early, and pregnant women must undergo early detection of pre-eclampsia. CONCLUSION: Pre-eclampsia is associated with various factors including maternal age, the number of previous pregnancies (parity), the interval between pregnancies, body mass index (BMI), obesity, a history of chronic health conditions, dietary habits, levels of physical activity, smoking status, nutritional well-being, attendance at antenatal care (ANC) visits, the presence of family support, as well as maternal knowledge and attitudes towards pregnancy.